Bacteria of Streptococcus Pneumonia - Samaher Adel Youssef Hussein; Zahraa Tahseen Ali Maki; Hinsha rahim judah duich; Roua Mahamed fadhel Abdelah; Zainab Kareem jabur saad (Genius Journals, 2024)
The upper respiratory tract is colonized by many microorganisms immediately after birth by transmission vertically from mother to child. The density of these germs decreases with the development of the immune system in adults, and some germs remain coexisting in the nasal cavity, including Actinobacteria, Bacteroidetes, Firmicutes, Bifidobacterium, Corynebacterium Streptococcus, Staphylococcus and rarely, fungi and viruses inhabit the respiratory tract. The pathogens of the respiratory system vary, as they are not limited to specific types of microorganisms, as they include many viruses and germs, and fungi and parasites record dangerous pathological conditions. Infections of the upper respiratory tract are less severe than those of the lower respiratory tract, and acute lower respiratory tract infections are the third major cause of human death worldwide, as the number of deaths reached3.2 million in 2015 and the number one cause of death for children under the age of five, according to the World Health Organization (WHO) 2017 (WHO). Acute lower respiratory tract infections are a major global health problem due to the emergence of antibioticresistant strains, which leads to recurrence of infection and the continuous spread of infection
Keywords: Streptococcus Pneumonia; upper respiratory tract